Evaluasi program pemberian MP-ASI bubuk instan dan biskuit di Kota Mataram, Kabupaten Lombok Barat, Lombok Timur dan Bengkulu Utara tahun 2007 - I Nyoman Adiyasa; Hamam Hadi; I Made Alit Gunawan (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2010)
Background: Increasing number of poor families leads to higher prevalence of malnourishment and malnutrition. The prevalence of malnutrition in children under five based on weight/age at the Province of Nusa Tenggara Barat and Bengkulu 2005 was above the national target. An effort made by the government to minimize the prevalence of malnourishment/ malnutrition is through the distribution of individual complementary breastfeeding for infants and children of 6-24 months old from poor families. The program had been implemented since 2003-2005 and there were problems of its implementation. In 2007 the program was re-implemented through the program of instant powder and biscuit complementary breastfeeding distribution but its achievement has never been evaluated.Objective: To evaluate the achievement of instant powder and biscuit complementary breastfeeding program at Mataram Municipality, District of Lombok Barat, Lombok Timur, and Bengkulu Utara 2007.Method: The study was observational with pre and posttest design using descriptive, analytical, quantitative, qualitative, and explorative approaches. Subjects were managers of complementary breastfeeding program at provincial, district/ municipal level, health centers, villages/integrated service post and program target. Variables of input, process, output and outcome were obtained through observation, filling in questionnaires, indepth interview, and secondary data recording. Data were analyzed descriptively, analytically, and qualitatively.Result: In the aspect of input, only human resources that was quantitavely adequate, and so were technical guideline at Lombok Timur, Complementary breastfeeding packages relevant with the quantity proposed at Bengkulu Utara. Budget for socialization and program guidebook at Bengkulu Utara were not available. Distribution method was relevant with the guidebook. In the aspect of process, planning was irrelevant with the guidebook; storage was 43.8% relevant with the requirement; distribution was 31.3% relevant with the schedule, quantity and types; monitoring was relevant with the schedule of integrated service post. In the aspect of output, the program was 78.8% relevant with target; 32.5% relevant with quantity; 95.6% could improve weight gain (p < 0.05). In the aspect of outcome: the program could overcome and prevent the prevalence of malnutrition, malnourishment and sustain good nutrition status as much as 55.6% and the result of Z-score statistical test was p < 0.05.Conclusion: Achievement of instant powder and biscuit complementary breastfeeding program in aspect of input was average at three districts/municipality and good at District of Lombok Timur and poor at District of Bengkulu Utara; in aspect of output was poor at three districts/municipality and average at District of Bengkulu Utara; in aspect of outcome was poor at all districts/municipality. There was difference in average weight target before and after the supply of complementary breastfeeding. There was difference in average Z score target before and after the supply of complementary breastfeeding.